Development of an Innovative Contextual Chemistry Textbook on Hydrocarbon Concepts : Enhancing Students' Mastery of Concepts - Pahriah Pahriah; Baiq Rina Amalia Safitri; Wirawan Putrayadi (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to develop an innovative contextual chemistry textbook on hydrocarbon concepts to enhance students' mastery of the subject. This research method used research and development with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The study was specifically confined to the development stage, as its primary focus is on assessing the validity of the developed products. The validation process involved two material expert validators, one media expert validator, one practitioner validator, and ten students from Ushuluddin NW Ubung Islamic Boarding School, who served as limited test validators. Quantitative data obtained from the feasibility validation results were analyzed using a percentage formula. Qualitative data in the form of responses and suggestions for improvement from validators are used as considerations for making revisions. The results showed that the validator assessment resulted in a very satisfactory average percentage, with material expert validators reaching 83% (very feasible category), media expert validators reaching 75% (feasible category), practitioner validators reaching 91% (very feasible category), and Limited student trials reached 89% (very feasible category). Therefore, this textbook successfully met high validity standards and can be considered suitable for use in the learning process.